Commentary: A New "Response" of the Congregation for the Doctrine of the Faith: Validity Baptism - Miralles, Antonio (Studies in church law, 2008)
Kommentar zur Entscheidung: Congregatio pro Doctrina Fidei, Responses to Questions on the Validity of Baptism, Studies in Church Law 4 (2008), 17-18.